E-module media and educational technology based on gamification for students of the Faculty of Tarbiyah and Teacher Training IAIN Palopo - Fakhrunnisaa, Nur; Edy, Marwan Ramdhany; Faisal, Dhia Azizah (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2025)
The research examines the development of gamification-based e-modules for media and educational technology, conducted at the Faculty of Tarbiyah and Teacher Training, IAIN Palopo, with 103 students as participants. This study employs a Research and Development (R&D) approach, utilising the ASSURE development model, which encompasses six stages: Analyse, State, Select, Utilise, Require, and Evaluate. Data collection methods include observation, questionnaires, documentation, and product validation. The researcher used both quantitative and qualitative analyses for data evaluation. The research resulted in creating a gamification-based e-module for media and educational technology, developed through the six stages of the ASSURE model. These stages involved needs analysis, development processes, and product finalisation. The product's validity was assessed by language experts (86.67%), media experts (88.89%), and material experts (97.12%), all indicating that the e-module is valid and suitable for use. The practicality test yielded a score of 79.76%, showing that the e-module is practical and effective in enhancing student learning.